Strategies on Learning Speaking used by International Accounting Students: (A Descriptive Quantitative Research at International Accounting Class of FEB Students in Universitas Tanjungpura Pontianak in academic year 2021) - Clarry Sada; Surmiyati; Endang Susilawati; Yanti Sri Rezeki; silvia (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research aimed to investigate the strategies that are used by the international accounting students at universitas Tanjungpura and to explain the most dominant learning speaking strategies used by international accounting students in learning speaking. The total numbers of participants in this research are 34 students. This research used a descriptive quantitative design, and the data were collected from questionnaires. The findings of this study revealed that international accounting students in the universitas Tanjungpura class used nearly all of the strategies for learning English. The highest average was Metacognitive strategy, with 52,0% total average. The second strategy is Cognitive strategies with the average 44,1%; the third strategy was effective strategy with the average 38,3%, the fourth strategy was the social strategy with the average 38,2%, fifth strategy was compensation with the average 33,8%, and the last strategy was memory strategy with average 11,0%.